2019
DOI: 10.1002/sim.8183
|View full text |Cite
|
Sign up to set email alerts
|

Impact of predictor measurement heterogeneity across settings on the performance of prediction models: A measurement error perspective

Abstract: It is widely acknowledged that the predictive performance of clinical prediction models should be studied in patients that were not part of the data in which the model was derived. Out‐of‐sample performance can be hampered when predictors are measured differently at derivation and external validation. This may occur, for instance, when predictors are measured using different measurement protocols or when tests are produced by different manufacturers. Although such heterogeneity in predictor measurement between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…Measurement heterogeneity refers to differences in the procedure and/or instruments used to measure the predictors. It has been shown that prognostic models including unreliable/misclassified predictors perform suboptimally on internal (271,272) and, especially, external validation (273)(274)(275). In prostate cancer, all standard variables used for developing prognostic models are known to be unreliably measured and/or are subject to measurement heterogeneity.…”
Section: Reliability and Measurement Heterogeneitymentioning
confidence: 99%
“…Measurement heterogeneity refers to differences in the procedure and/or instruments used to measure the predictors. It has been shown that prognostic models including unreliable/misclassified predictors perform suboptimally on internal (271,272) and, especially, external validation (273)(274)(275). In prostate cancer, all standard variables used for developing prognostic models are known to be unreliably measured and/or are subject to measurement heterogeneity.…”
Section: Reliability and Measurement Heterogeneitymentioning
confidence: 99%
“…Furthermore, we take the position that addressing measurement heterogeneity at the data collection stage is preferred over statistical correction for measurement error in predictors. Correctionsdtypically aiming to alleviate measurement-error bias in regression coefficientsdmay increase rather than reduce the measurement heterogeneity [12].…”
Section: Discussionmentioning
confidence: 99%
“…We refer to these differences in measurement across settings as predictor measurement heterogeneity. Simulation studies have shown that predictor measurement heterogeneity can induce miscalibration of prediction models and affect discrimination and accuracy at external validation [12]. Although predictor measurement heterogeneity across derivation and validation samples appears to be common in clinical (research) settings (see, e.g., studies by Collins et al [4], Te Velde et al [15], and Smith et al [16]), its impact on the performance of prediction models at validation is not well studied using empirical data.…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%
“…Besides, inter-observer variation in pathological examination of BC among studies may lead to different adjuvant systemic therapy advice and, consequently, prediction of CBC risk [23]. Variation in prediction performance and limited generalizability of CBC risk calculators can also be partially explained by differences in how predictors are measured among studies [24,25]. For example, lack of family history knowledge may lead to uncertainty in risk prediction and varies according to demographics of the patients [26].…”
Section: Discussionmentioning
confidence: 99%